Extraction of exopolymers from biofilms: the protective effect of glutaraldehyde - Azeredo, Joana (2003)
The extraction of the exopolymeric matrix is a prerequisite to properly assessing the composition of the biofilm. Several extraction methods have already been developed, however, no universal method has yet been adopted because the compromise between high yields of extraction and minimum cell lysis is difficult to establish. In fact, most of the extraction methods promote leakage of intracellular material. The most common extraction methods, Dowex resin and sonication, were assayed in biofilms of Pseudomonas fluorescens and Alcaligenes denitrificans submitted to a pre-treatment with glutaraldehyde (GTA). The assessment of ATP released after extraction was used as a criterion of cell lysis. The results showed that GTA is a protective agent against cell lysis. The pre-treatment with GTA is particularly useful combined with sonication.